Cross-Cultural Validity, Reliability, and Psychometric Properties of the Persian Version of the Scales for Outcomes in Parkinson's Disease-Psychosocial Questionnaire. (7th April 2014) - Fereshtehnejad, Seyed-Mohammad; Farhadi, Farzaneh; Hadizadeh, Hasti; Shahidi, Gholam Ali; Delbari, Ahmad; Lökk, Johan
Abstract : Objectives . Considering the influence of different motor and nonmotor features of Parkinson's disease (PD), it is important to evaluate the psychosocial functioning of the patients. For this purpose, the scales for outcomes in Parkinson's disease-psychosocial questionnaire (SCOPA-PS) has been previously designed. The aim of our study was to assess the cross-cultural validation and psychometric properties of the Persian version of the SCOPA-PS. Methods . One hundred and ten nondemented idiopathic Parkinson's disease (IPD) patients were consecutively recruited from an outpatient referral movement disorder clinic. Eligible patients filled up a number of questionnaires including the Persian version of SCOPA-PS during the face-to-face interview session and clinical examination to measure disease severity, nonmotor psychiatric symptoms, and health-related quality of life (HRQoL). Results . The highest and lowest correlation coefficients of internal consistency were reported for item 7 on " asking for help " ( r = 0.765 ) and item 5 on " sexual problems " ( r = 0.553 ) . Cronbach's alpha reliability coefficient of the entire scale was 0.87 (95% CI: 0.83–0.90). The Hoehn and Yahr stage ( r = 0.34, P < 0.001 ), Schwab and England ADL scale ( r = - 0.55, P < 0.001 ), anxiety ( r = 0.64, P < 0.001 ), depression ( r = 0.71, P < 0.001 ), and fatigue ( r = 0.35, P < 0.001 ) were significantly correlated with the total score of the SCOPA-PS questionnaire. Conclusions . The Persian version of SCOPA-PS is a highly reliable and valid scale to measure psychosocial functioning in IPD patients with different sex, age-group, and educational level, which could be applied in future researches. Disease severity scales, depression, anxiety, fatigue, and different domains of HRQoL were all associated with psychosocial functioning in PD patients.